Encoding Crime and Punishment in TEI: The Digital Processing of Early Modern Broadsheets from Vienna - Claudia Resch; Daniel Schopper; Tanja Wissik; Daniela Fasching (Journal of the Text Encoding Initiative, 2019)
In this project note, we introduce a set of printed single broadsheets in German, recently discovered in two of Vienna’s libraries, which, thanks to their digitization, annotation, and online publication by the Austrian Centre for Digital Humanities (ACDH) at the Austrian Academy of Sciences (ÖAW), promise to shed new light on the history of crime and punishment in early modern Vienna. The broadsheets, entitled “Death Sentences,” belong to a little-explored genre of print media distributed to advertise public executions and have not been subject to closer scholarly examination before now. In their investigation of the sources, the ACDH employs a mixed-method approach combining traditional and digital methods. The sources are transcribed and encoded according to the TEI Guidelines, making use, in particular, of the namesdates module to capture essential information about the convicts sentenced to death. The following description gives an overview of the encoding schemes applied and the research possibilities resulting from the use of these methods, and outlines the functionalities of the planned open-access edition. By making the processed and enriched data available to the public, we hope to pave the way for a comprehensive and interdisciplinary analysis of the sources, and to open up an interesting chapter of Viennese history to new audiences.